2009
DOI: 10.1007/s10900-008-9138-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Hepatitis B Lay Health Worker Intervention for Chinese Americans and Canadians

Abstract: Hepatitis B testing is recommended for immigrants from countries where hepatitis B infection is endemic. However, only about one-half of Chinese in North America have received hepatitis B testing. We conducted a randomized controlled trial to evaluate the effectiveness of a hepatitis B lay health worker intervention for Chinese Americans/Canadians. Four hundred and sixty individuals who had never been tested for hepatitis B were identified from community-based surveys of Chinese conducted in Seattle, Washingto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 20 publications
4
47
2
Order By: Relevance
“…First, the results of this study were based on self-reported data. As with other studies that did not verify the validity of self-reported HBV screening behavior, 30,31 the present study lacked the resources to verify the self-reported screening with medical records, especially for HBV screening that took place in the patients’ home countries. Second, because of the cross-sectional nature of the data, we were unable to follow up on whether participants who reported susceptibility to future HBV infection subsequently received a complete series of hepatitis B vaccinations.…”
Section: Discussionmentioning
confidence: 99%
“…First, the results of this study were based on self-reported data. As with other studies that did not verify the validity of self-reported HBV screening behavior, 30,31 the present study lacked the resources to verify the self-reported screening with medical records, especially for HBV screening that took place in the patients’ home countries. Second, because of the cross-sectional nature of the data, we were unable to follow up on whether participants who reported susceptibility to future HBV infection subsequently received a complete series of hepatitis B vaccinations.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, 85% of contactable individuals agreed to complete a home visit, and there was no meaningful difference in the proportions of men (82%) and women (88%) who agreed to complete a home visit. An earlier study evaluated a CHW intervention for Chinese immigrants to the Pacific Northwest, and found that the proportions of men and women that were prepared to participate in educational sessions about HBV were 74% and 66%, respectively (Taylor et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…In Canada, CHWs are often compensated by the health organization for which they are working. 13,17,20,25 They are either employed full-time or part-time, 13,20 or remunerated for specific services, 25 although some work as volunteers. 14,26 Sometimes public health departments support a particular public health program financially but do not pay wages for CHWs.…”
Section: Education and Trainingmentioning
confidence: 99%
“…Much of the literature describes CHR programs targeting the Aboriginal population [12][13][14]20,31 or the role of CHRs in improving social capital, cohesion and social support as important determinants of Aboriginal health. 2,32,33 Other studies have documented the role of CHWs in maternal health programs, 15,22 dental health for preschool children, 18 hepatitis B testing, 25 HIV/AIDS prevention, 27 community development more generally 16 and nutrition programs. 17 In addition, for research purposes, CHWs are employed to collect data from the communities they serve 15,18,22,34 or are identified as key informants regarding those communities.…”
Section: Education and Trainingmentioning
confidence: 99%